TRATAMENTO DE ÁGUA DE LAVAGEM DE FILTRO POR SEDIMENTAÇÃO SIMPLES E ASSISTIDA POR COAGULANTE RECUPERADO DE LODO DE DECANTADOR DE ESTAÇÃO DE TRATAMENTO DE ÁGUA - GOLINSKI, ELAINE (2023)
In Brazil, the improper disposal of sludge from Water Treatment Plants (WTPs) poses a significant environmental challenge. This study focuses on the recovery of coagulants from decanter sludge, a sustainable approach that could reduce environmental impacts and optimize resources in water treatment. The primary objective of this work was to investigate the effectiveness of recovering and reusing coagulants from decanter sludge, aiming at the treatability of filter backwash water in WTPs. A bench-scale experimental procedure was used, including Jar-Test trials, to evaluate the coagulant recovery under various operational conditions. These tests used filter backwash water samples from two different WTPs. The parameters analyzed in these experiments were turbidity, apparent color, and pH. In addition to trials with the recovered coagulant, experiments were also conducted with the commercial coagulant PAC for comparative purposes. Finally, trials without coagulant addition were carried out to verify the efficiency of sedimentation alone in treating the studied filter backwash waters. The results demonstrated that the recovered coagulant was effective in reducing the turbidity of the filter backwash water, achieving significantly low residual values under the best operational conditions. For instance, a residual turbidity of 9.3 NTU was noted with a 10 mgAl/L dosage of the recovered coagulant after 15 minutes of sedimentation and 4.5 NTU after 30 minutes for the Ponta Grossa filter backwash water. For the Irati filter backwash water, a residual turbidity of 6.1 NTU was observed after 15 minutes and 2.6 NTU after 30 minutes. It is concluded that the recovery of coagulants from decanter sludge is a viable and efficient strategy, offering a sustainable solution for the treatment of backwash water in WTPs, with potential for safe recirculation or even reuse.